Developmental evaluation: Bridging the gaps between proposal, program, and practice , Developmental evaluation: Bridging the gaps between pr oposal, program, and practice - Lawrence, Rachael B.; Rallis, Sharon F.; Davis, Laura C.; Harrington, Karen (Evaluation, 2018)
Developmental evaluation supports grant-funded initiatives seeking inn ovation and change. Programs born from aspirational grant language and plans often need guidance as they work toward creating workable model s for social innovation. This article describes the challenge of desig ning and implementing complex programs and presents a case that illust rates how a program moves from proposal to practice. The Massachusetts Charter Public School Association Capacity Building Network is a comp lex intervention, funded by the US federal government, aimed at raisin g school capacity to serve students with disabilities and English lang uage learners. Developmental evaluation served to bridge the gaps betw een an aspirational proposal, an ambitious and ambiguous program plan, and emerging practices to serve this population of students. Jointly reviewing our experience in this developmental evaluation, the evaluat ion team and a program director share important thematic lessons learn ed about the developmental evaluation approach., Developmental evaluat ion supports grant-funded initiatives seeking innovation and change. P rograms born from aspirational grant language and plans often need gui dance as they work toward creating workable models for social innovati on. This article describes the challenge of designing and implementing complex programs and presents a case that illustrates how a program m oves from proposal to practice. The Massachusetts Charter Public Schoo l Association Capacity Building Network is a complex intervention, fun ded by the US federal government, aimed at raising school capacity to serve students with disabilities and English language learners. Develo pmental evaluation served to bridge the gaps between an aspirational p roposal, an ambitious and ambiguous program plan, and emerging practic es to serve this population of students. Jointly reviewing our experie nce in this developmental evaluation, the evaluation team and a progra m director share important thematic lessons learned about the developm ental evaluation approach.